Effect of Plane of Nutrition on Nutrient Utilization in Pre-partum Murrah Buffaloes and Birth Weight of Their Calves - Srividhya, S.; Malik, R.; Naliyapara, H.B.; Dey, Dipak (Indian Journal of Animal Nutrition, 2022)
The present study was conducted to ascertain the effect of feeding a higher level of metabolizable energy and metabolizable protein on feed intake, nutrient utilization, and optimizing their calves' birth weight. Eighteen pregnant Murrah buffaloes in the last trimester of pregnancy were distributed into three groups (n=6) based on average body weight (629.69Â±15.05) Kg and Lactation number (3.27Â±0.05). The feeding trial was conducted 90 days before prepartum. T1 (Control) was fed as per ICAR (2013) nutrient requirements recommendation whereas T2 (HME) were offered 30% higher energy and T3 (HMP) were offered 40 % higher protein than ICAR (2013) nutrient requirements recommendation. Concentrate mixture and green fodder were offered to an individual animal as per experiment protocol. Dry matter intake (DMI) was almost similar in all groups. Average daily body weight gain was higher (P